The Amole Salt Metaphor: Cultural Resilience and National Cohesion in Ethiopian History - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR-Publisher), 2025)
This study develops a novel analytical framework using Amole salt, the historical currency and cultural object of Ethiopia, as a metaphor for understanding cultural resilience and political cohesion. Through multi-modal analysis of historical records, material properties, and socio-economic functions, demonstrate how Amole's physical characteristics (large size, high density, and slow solubility) provide a coherent model for Ethiopian endurance against external pressures. The large size (∼10×4×2 inches) metaphorically represents institutional scale that resists fragmentation; the high density (2.16 g/cm³) symbolizes social cohesion that prevents disintegration; and the slow dissolution rate embodies adaptive resilience that preserves cultural core identity while permitting gradual integration of external influences. The findings reveal that Amole salt functioned as what terms a